A new longhorn beetle (Coleoptera: Cerambycidae) from the Early Cretaceous Jehol Biota of Western Liaoning in China. (January 2015) - Yu, Yali; Ślipiński, Adam; Reid, Chris; Shih, ChungKun; Pang, Hong; Ren, Dong
Abstract: Pre-Cenozoic representatives of the coleopteran family Cerambycidae are practically little known. The discovery of a well-preserved fossil of longhorn beetle in the Lower Cretaceous (about 122 Ma) lacustrine deposits of the Yixian Formation in Western Liaoning, China, is the second record of Mesozoic Cerambycidae. We assign this specimen to a new genus and species, Sinopraecipuus bilobatus gen. et sp. nov., but are unable to place it with confidence in any existing subfamily of Cerambycidae due to the insufficient morphological evidence available from the specimen.